Discrimination and Inequality in an Integrated Walrasian-General-Equilibrium and Neoclassical-Growth Theory - Zhang, Wei-Bin (Asian Journal of Economic Modelling, 2016)
The purpose of this study is to examine dynamic interdependence between economic development, wealth and income distributions, and discrimination in an integrated Walrasian-general-equilibrium and neoclassical-growth theory. We build a dynamic economy with one consumer goods sector, one capital goods sector, and heterogeneous households. We build a model in which wealth accumulation, income and wealth distribution, time distribution and division of labor interact with each other under a fixed pattern of discrimination. For illustration, we simulate the motion of the economic system with three groups, called the discriminator, the neutral group (neither discriminating nor being discriminated), and the discriminated group. We identify the existence of a unique stable equilibrium point. Our comparative dynamic analyses with regard to different discrimination rates provide some insights. For instance, we show that when the discriminator strengthens its discrimination against the discriminated group and the discriminated group “positively” reacts the strengthened discrimination, we have the following effects: the national output, the national wealth, the total labor supply, and the output levels and the input factors of the two sectors are increased; the lump sum transfer from the discriminated group to the discriminator is increased; the discriminated group’s wage rate is augmented and the other two groups’ wage rates are slightly affected; the discriminator’s work time is reduced, the discriminated group’s work time is increased, and the neutral group’s work time is slightly affected; the discriminated group’s and the discriminator’s consumption and wealth levels are increased, and the neutral group’s consumption and wealth levels are slightly affected.